Livestock and sustainable food systems: Status, trends, and priority actions - Herrero, Mario; Mason-D'Croz, Daniel; Thornton, Philip K.; Fanzo, J.; Rushton, Jonathan; Godde, Cecile M.; Bellows, A.; Groot, A. de; Palmer, J.; Jinfeng Chang; Zanten, H. van; Wieland, Barbara; et al. (Springer, 2023)
Livestock are a critically important component of the food system, although the sector needs a profound transformation to ensure that it contributes to a rapid transition towards sustainable food systems. This chapter reviews and synthesises the evidence available on changes in demand for livestock products in the last few decades, and the multiple socio-economic roles that livestock have around the world. We also describe the nutrition, health, and environmental impacts for which the sector is responsible. We propose eight critical actions for transitioning towards a more sustainable operating space for livestock. (1) Facilitate shifts in the consumption of animal source foods (ASF), recognising that global reductions will be required, especially in communities with high consumption levels, while promoting increased levels in vulnerable groups, including the undernourished, pregnant women and the elderly. (2) Continue work towards the sustainable intensification of livestock systems, paying particular attention to animal welfare, food-feed competition, blue water use, disease transmission and perverse economic incentives. (3) Embrace the potential of circularity in livestock systems as a way of partially decoupling livestock from land. (4) Adopt practices that lead to the direct or indirect mitigation of greenhouse gases. (5) Adopt some of the vast array of novel technologies at scale and design incentive mechanisms for their rapid deployment. (6) Diversify the protein sources available for human consumption and feed, focusing on the high-quality alternative protein sources that have lower environmental impacts. (7) Tackle antimicrobial resistance effectively through a combination of technology and new regulations, particularly for the fast-growing poultry and pork sectors and for feedlot operations. (8) Implement true cost of food and true-pricing approaches to ASF consumption.